Histaminergic and non‐histaminergic elicited itch is attenuated in capsaicin‐evoked areas of allodynia and hyperalgesia: A healthy volunteer study. (17th February 2017) - Andersen, H.H.; Elberling, J.; Sharma, N.; Hauberg, L.E.; Gazerani, P.; Arendt‐Nielsen, L.
Abstract: Background: Chronic pain patients with sensitization may exhibit decreased sensitivity to normally pruritogenic sensory stimuli and moreover occasionally perceive these as painful. This study explored the relationship between itch and pain, by evaluating histaminergic and non‐histaminergic itch evoked in capsaicin‐induced allodynic and hyperalgesic areas. Methods: In 28 healthy volunteers, capsaicin (100 μg/0.1 mL) was injected intradermally in the volar forearm to establish secondary dysesthesias. After the capsaicin‐induced pain subsided, the areas of allodynia and hyperalgesia were mapped and itch was provoked inside these areas by histamine (10 mg/mL) and cowhage (25–40 spicules). The evoked itch and pain were recorded on a visual analogue scale (VAS 0–10 cm). Contralateral injection of 0.1 mL isotonic saline served as a control. Results: Histaminergic and non‐histaminergic evoked itch were significantly decreased when provoked in allodynic skin ( p < 0.05). The area‐under‐the‐curve of the evoked itch was reduced −43% from 18.0 ± 2.6 cm 10 min in normal skin to 10.3 ± 1.8 cm 10 min in allodynic skin ( p < 0.01) for cowhage and −56% from 20.0 ± 3.5 cm 10 min in normal skin to 8.8 ± 2.3 cm 10 min allodynic skin ( p < 0.001) for histamine. The pain responses to the pruritogens were not significantly altered between the areas of allodynia and normal skin ( p > 0.1). An additional experiment showed that pinprick hyperalgesia in the absence of allodynia was sufficient to evoke the observed reduced sensitivity to itch stimuli. Conclusions: Cutaneous sensitization (secondary allodynia and hyperalgesia) reduced itch responses regardless of the type of itch model applied and without attenuation of the associated pruritogen‐induced pain responses. This could explain the decreased sensitivity to itch provocations previously observed in patients with chronic pain. Significance: This study shows that the neuronal sensitization processes underlying the development secondary hyperalgesia involve significant gating of histaminergic as well as non‐histaminergic pruriceptive transmission. Because these itch provocations normally target specific subpopulations of C‐nociceptors they could be of relevance for exploratory purposes in pain patients.